Activity-based protein profiling reveals deubiquitinase and aldehyde dehydrogenase targets of a cyanopyrrolidine probe. Issue 11 (13th September 2021) - Panyain, Nattawadee; Godinat, Aurélien; Thawani, Aditya Raymond; Lachiondo-Ortega, Sofía; Mason, Katie; Elkhalifa, Sarah; Smith, Lisa M.; Harrigan, Jeanine A.; Tate, Edward W.
Abstract : We report the characterization of a UCHL1 covalent inhibitor based on a thiazole cyanopyrrolidine scaffold and a closely-related activity-based probe (ABP) which was used to generate a quantitative profile for on- and off-targets in human cells. Abstract : Ubiquitin carboxy-terminal hydrolase L1 (UCHL1), a deubiquitinating enzyme (DUB), is a potential drug target in various cancers, and liver and lung fibrosis. However, bona fide functions and substrates of UCHL1 remain poorly understood. Herein, we report the characterization of UCHL1 covalent inhibitor MT16-001 based on a thiazole cyanopyrrolidine scaffold. In combination with chemical proteomics, a closely related activity-based probe (MT16-205 ) was used to generate a comprehensive quantitative profile for on- and off-targets at endogenous cellular abundance. Both compounds are selective for UCHL1 over other DUBs in intact cells but also engage a range of other targets with good selectivity over the wider proteome, including aldehyde dehydrogenases, redox-sensitive Parkinson's disease related protein PARK7, and glutamine amidotransferase. Taken together, these results underline the importance of robust profiling of activity-based probes as chemical tools and highlight the cyanopyrrolidine warhead as a versatile platform for liganding diverse classes of protein with reactive cysteine residues which can be used for further inhibitor screening, and as a starting point for inhibitor development.